Sociodemographic and Behavioral Factors Associated with HIV Vulnerability according to Sexual Orientation - Maria Aparecida A. O. Serra; Antoninho B. Milhomem; Samae B. Oliveira; Francisca Aline A. S. Santos; Roberta Araújo e Silva; Ana Cristina P. J. Costa; Maria da Conceição S. O. Cunha; Antônio Uelton A. Silva; Roberto Wagner J. F. Freitas; Márcio Flávio M. Araújo (AIDS Research and Treatment)
Objective. To analyze sociodemographic and behavioral factors associated with vulnerability to HIV according to sexual orientation. Method. This is a cross-sectional study conducted using data on 3,818 people in the city of Imperatriz, Brazil, during 2015 and 2016. The survey’s questionnaires addressed sociodemographic and behavioral variables. For the data analysis, association (chi-square test) and strength of association (odds ratio) were observed. A significance level of p<0.05 and adjustment for age and gender were taken into consideration. Results. A substantial portion of the sample stated they were heterosexual (88.8%). These individuals demonstrated a lower chance of HIV infection (p<0.001), sexually transmitted infections (p<0.001), alcohol use (p<0.001) and condom use (p<0.001), compared to men who have sex with men and/or bisexuals. In this group, after adjusting for confounding variables, the factors associated with HIV infection were being male (p<0.001), unmarried (p<0.001), having completed higher education (p<0.001) and boasting multiple sexual partners (p<0.001). Conclusion. Behavioral and sociodemographic factors of vulnerability to HIV are predominant among men who have sex with men and/or are bisexual.